Parathyroid glands autotransplantation in the postoperative hypoparathyroidism prevention - O. S. Popov; S. V. Logvinov; N. I. Lyan; M. M. Larionov; A. N. Galyan; S. N. Gasparyan; R. Ya. Geydarov; Ye. V. Galyan; A. N. Baikov; V. V. Udut (Бюллетень сибирской медицины, 2011)
The surgery results analysis of 615 patients with various thyroid disorders was carried out. The percentage of postoperative hypoparathyroidism amounted 1,14%. In order to prevent postoperative hypoparathyroidism in the course of experiment, the method of endovascular autotransplantation of accidentally removed or deprived of supply parathyroid glands was developed.